Development of a control support system for smart homes using the analysis of user interests based on mixed reality - Yuka Sone; Chifuyu Matsumoto; Jinseok Woo; Yasuhiro Ohyama (ROBOMECH Journal)
Abstract In recent years, IoT technologies have made our daily lives more convenient and comfortable. In particular, these technologies are being actively utilized in our living environments through the development of various smart home appliances. As the pace of Digital Transformation (DX) quickens and digital platforms become integrated into diverse residential settings, the notion of the home we inhabit is taking on greater significance beyond merely a place for rest. Therefore, this paper explains the development of user-friendly interfaces for smart home systems used in our living rooms. An appropriate service can be provided accordingly if the user’s intent is specifically understood. Therefore, this paper explores the relationship between the user’s gaze and the control targets of the smart home using Mixed Reality (MR) devices. In this study, we introduce a novel smart home control system from a range of options. Our proposed system enables user analysis and remote control through the utilization of an MR device capable of tracking a user’s gaze. In addition, we investigate the perception of user interfaces and analyze the survey results conducted after using the interface system, discussing the validity of the proposed system.